Complete mitochondrial genome of banana skipper Erionota torus Evans (Lepidoptera: Hesperiidae) and phylogenetic analysis - Liu, Li-Na; Zeng, Li; Guo, Zhi-Xiang; Yang, Bao-Ming; Yin, Ke-Suo; Wang, Chun-Mei; Zheng, Si-Jun (Informa UK Limited, 2021)
Erionota torus (Evans, 1941) is a banana pest and is mainly distributed in Southeast Asia and the Pacific regions. The complete mitogenome of E. torus (GenBank accession number MW586888) is 15,987 bp in size, including 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNAs genes, and a noncoding A þ T-rich region. The A þ T-rich region is located between 12S rRNA and tRNAMet. The base compos ition of the whole E. torus mitogenome is 39.68% for A, 7.30% for G, 41.55% for T, and 11.47% for C, with a high AT content of 81.23%. The phylogeny analysis indicated that E. torus had a close relation ship with Notocrypta curvifascia. The present data could contribute to the further detailed phylogeo graphic analysis and provide a comprehensive control strategy for this banana pest.